Aplikasi Marketplace Vendor Lamaran dan Pernikahan berbasis Android - Yansen Tri Utomo; Silvia Rostianingsih; Leo Willyanto Santoso (Jurnal Infra, 2022)
In the world of marriage or application, it is something that takes quite a long time, especially in choosing vendors, venues, and WO. With the Mywedding mobile application, it is made to assist in choosing any vendors that can be used for their wedding or application as well as provide the best recommendations according to the criteria of everyone who will prepare for a wedding. Content based filtering method used to collect data and assess suitable vendors to be recommended by the system to users. Based on the results of the tests carried out, the content-based filtering method succeeded in providing recommendations according to the wishes of the user so that they can find out which vendor can be used, although sometimes the user profile needed is more specific to be more accurate. which can be used for their wedding or proposal and provide the best recommendations that match the criteria of everyone who will prepare for a wedding. Content based filtering method used to collect data and assess suitable vendors to be recommended by the system to users.